Angular Dependence of Hysteresis Shift in Oblique Deposited Ferromagnetic/Antiferromagnetic Coupled Bilayers - Aliaga-Vidal, C; Aliaga-Vidal, C; Casagrande-Denardin, J (American Institute of Physics, 2014)
The angular dependence of the hysteresis shift has been investigated in ferromagnetic/antiferromagnetic (NiFe/IrMn) bilayers grown by oblique deposition under the influence of a static magnetic field applied perpendicular to the uniaxial anisotropy direction induced during the growth process. It was found that at low oblique deposition angles, the unidirectional anisotropy field is much greater than the uniaxial anisotropy field and the corresponding anisotropies directions are noncollinear. In these conditions, the angular dependence of the hysteresis loop shift exhibits the well know cosine like shape but demanding a phase shift. Contrary to this, at high oblique deposition angle (70°), the uniaxial anisotropy plays the fundamental role and the anisotropies directions are collinear. In this case, the exchange bias displays a jump phenomenon. The numerical calculations are consistent with the experimental data obtained from magneto-optical Kerr effect and ferromagnetic resonance. © 2014 AIP Publishing LLC.